2018
DOI: 10.1159/000491658
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Nrf2-ARE Pathway Ameliorates Hyperglycemia-Mediated Mitochondrial Dysfunction in Podocytes Partly Through Sirt1

Abstract: Background/Aims: Previously we have shown that activation of the nuclear factor (erythroid-derived 2)-like 2 (Nrf2)-antioxidant response element (ARE) attenuated hyperglycemia-induced damage in podocytes, but the molecular mechanism remains unknown. Methods: Tert-butylhydroquinone (t-BHQ) and small interfering RNAs (siRNAs) were used to regulate Nrf2 expression, while nicotinamide and siRNAs were used to regulate sirtuin 1 (Sirt1) activity and expression, respectively. Mitochondrial superoxide, membrane potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…5a, b ). Consistent with our previous report 19 , 20 , cultured human podocytes were injured by HG, as demonstrated by lower expression of Nephrin and Synaptopodin (Fig. 5c, e ).…”
Section: Resultssupporting
confidence: 93%
“…5a, b ). Consistent with our previous report 19 , 20 , cultured human podocytes were injured by HG, as demonstrated by lower expression of Nephrin and Synaptopodin (Fig. 5c, e ).…”
Section: Resultssupporting
confidence: 93%
“…In the present study, the activation of Sirt1 with SRT1720 inhibited EC apoptosis and endothelial dysfunction in diabetes. Previous reports have argued that the protective endothelial effect of Sirt1 is closely associated with the regulation of mitochondrial functions by limiting mitochondrial DNA damage and preventing the activation of mitochondrial damaging MMP-9 (11,43,44). Furthermore, mitochondrial dysfunction caused by mitochondrial fission is reported to be involved in the development of diabetic nephropathy (7,45) and diabetic cardiomyopathy (46).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, SIRT1 is mainly expressed in neurons and has numerous biological functions, including regulation differentiation, metabolism, cell survival, and aging (Qadir and Anwar, 2017). It has been reported that SIRT1 activation attenuates hyperglycemia and plays an important mediatory role in treating diabetic complication (Li X. N. et al, 2017; Zhang Q. et al, 2018; Zhang Y. et al, 2018). Furthermore, SIRT1 improves autophagic flux (Zhang et al, 2016; Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%